2013
DOI: 10.1155/2013/378298
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Qiliqiangxin Capsule on Energy Metabolism and Myocardial Mitochondria in Pressure Overload Heart Failure Rats

Abstract: Qiliqiangxin capsule (QL) was developed under the guidance of TCM theory of collateral disease and had been shown to be effective and safe for the treatment of heart failure. The present study explored the role of and mechanism by which the herbal compounds QL act on energy metabolism, in vivo, in pressure overload heart failure. SD rats received ascending aorta constriction (TAC) to establish a model of myocardial hypertrophy. The animals were treated orally for a period of six weeks. QL significantly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 17 publications
1
50
0
Order By: Relevance
“…18) CPT-1 is involved in fatty acid oxidation 19) and GLUT4 plays an important role in the oxidation of glucose. 20) To determine the potential mechanisms underlying the protective effects of ALLO, the mRNA expression of molecular markers (XO, PGC-1α, CPT-1, and GLUT4) was subjected to qRT-PCR analysis in the sham, AMI and ALLO groups. As depicted in Figure 4 (compared with the sham group, the mRNA expression of XO increased by 152.56% and 377.86% in the ALLO and AMI groups (P < 0.05); the mRNA expression of GLUT4 increased by 87.94% and 195.25% (P < 0.05); the mRNA expression of PGC-1α decreased by 50.31% and 84.42% (P < 0.05); and the mRNA expression of CPT-1 decreased by 24.76% and 54.45% (P < 0.05)).…”
Section: He Staining and Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
See 2 more Smart Citations
“…18) CPT-1 is involved in fatty acid oxidation 19) and GLUT4 plays an important role in the oxidation of glucose. 20) To determine the potential mechanisms underlying the protective effects of ALLO, the mRNA expression of molecular markers (XO, PGC-1α, CPT-1, and GLUT4) was subjected to qRT-PCR analysis in the sham, AMI and ALLO groups. As depicted in Figure 4 (compared with the sham group, the mRNA expression of XO increased by 152.56% and 377.86% in the ALLO and AMI groups (P < 0.05); the mRNA expression of GLUT4 increased by 87.94% and 195.25% (P < 0.05); the mRNA expression of PGC-1α decreased by 50.31% and 84.42% (P < 0.05); and the mRNA expression of CPT-1 decreased by 24.76% and 54.45% (P < 0.05)).…”
Section: He Staining and Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Inside the cell, glucose is phosphorylated to glucose-6-phosphate, which subsequently enters glycolysis via phosphofructokinase I. Pyruvate, the end product of glycolysis, is taken up into the mitochondria and converted into acetyl-CoA by pyruvate dehydrogenase (PDH) to enter the Krebs cycle. GLUT4 is the key enzyme of glucose oxidation; 20) acetyl-CoA is the common product of glycolysis and FAO; the Krebs cycle produces NADH and FADH, which feed their electrons into the ETC and drive oxidative phosphorylation (as depicted in Figure 7). …”
Section: He Staining and Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
See 1 more Smart Citation
“…The other cardioprotective effects of qili-qiangxin were related to the regulation of the glycolipid substrate metabolism by activating AMPK (AMP-activated protein kinase)/PGC-1α (peroxisome proliferators-acti- vated receptor-γ coactivator-1α) axis. Also, it was suggested that qili-qiangxin reduced the accumulation of free fatty acids and lactic acid protecting cardiac myocytes and mitochondrial function [38].…”
Section: Qili-qiangxin Capsulesmentioning
confidence: 99%
“…Protective effects of QL were demonstrated by a multicenter randomized double‐blind clinical study including 512 heart failure patients 19. It was also reported that QL could improve cardiomyocyte metabolism and inhibit cardiomyocyte apoptosis 20, 21, 22, 23. Our previous work found that QL could promote cardiac angiogenesis and up‐regulate HIF‐1α expression in failing heart and hypoxic CMECs via NRG‐1/ErbB‐PI3K/Akt/mTOR pathway, thus promoting cardiac angiogenesis 24, 25.…”
Section: Introductionmentioning
confidence: 97%